Low Pepsinogen I/II Ratio and High Gastrin-17 Levels Typify Chronic Atrophic Autoimmune Gastritis Patients With Gastric Neuroendocrine Tumors. Issue 9 (15th September 2020) - Magris, Raffaella; De Re, Valli; Maiero, Stefania; Fornasarig, Mara; Guarnieri, Giovanni; Caggiari, Laura; Mazzon, Cinzia; Zanette, Giorgio; Steffan, Agostino; Canzonieri, Vincenzo; Cannizzaro, Renato
Abstract : INTRODUCTION: Chronic atrophic autoimmune gastritis (CAAG) can lead to the development of gastric neuroendocrine tumors (gNETs) and can be accompanied by other autoimmune diseases. This study aimed to determine, in CAAG patients, the association of gNET development, the prevalence of autoimmune diseases other than CAAG, the association of autoimmunity, and gNET development with pepsinogen I, II, gastrin-17, and Helicobacter pylori infection analysis. METHODS: We determined the prevalence of gNETs and other autoimmune diseases and analyzed pepsinogen I and II, gastrin-17 serum levels, and H. pylori infection in all patients diagnosed with CAAG at our hospital between 2013 and 2017. RESULTS: A total of 156 patients were studied and in 15.4% was observed concomitant gNET. Approximately 68.6% had at least 1 other autoimmune disease at diagnosis of CAAG. Approximately 60.9% had autoimmune thyroiditis, followed by diabetes (19.9%) and autoimmune polyendocrine syndrome (12.8%). CAAG patients with and without gNET had similar rates of comorbidity with other autoimmune diseases, but the pepsinogen I/II ratio was lower in patients with gNET (1.6 vs 4.5, P = 0.018). Receiver operating characteristic curve analyses identified a pepsinogen I/II ratio <2.3 and gastrin-17 levels >29.6 pmol/L as cutoffs distinguishing CAAG patients with gNET from those without. The combined use of these cutoff correctly identified 16 of the 18 CAAG patients with gNET ( P = 0.007). H. pylori infection was observed in 28.7% of cases tested but did not associate with gNET. DISCUSSION: This study suggests that a low pepsinogen I/II ratio and high gastrin-17 levels characterize patients with CAAG and gNET and confirms the frequent coexistence of CAAG with other autoimmune diseases.